2018
DOI: 10.1016/j.molcel.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic View of hnRNPA2 Low-Complexity Domain Structure, Interactions, and Phase Separation Altered by Mutation and Arginine Methylation

Abstract: hnRNPA2, a component of RNA-processing membraneless organelles, forms inclusions when mutated in a syndrome characterized by the degeneration of neurons (bearing features of amyotrophic lateral sclerosis [ALS] and frontotemporal dementia), muscle, and bone. Here we provide a unified structural view of hnRNPA2 self-assembly, aggregation, and interaction and the distinct effects of small chemical changes-disease mutations and arginine methylation-on these assemblies. The hnRNPA2 low-complexity (LC) domain is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
417
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 356 publications
(443 citation statements)
references
References 67 publications
26
417
0
Order By: Relevance
“…At low CTD concentrations (50 µM and below) the apparent diffusion coefficient for WT CTD remains largely unchanged (8.8± 0.1 · 10 -11 m 2 s -1 ) ( Figure 3C), suggesting that this value reflects the diffusion coefficient of monomeric CTD. This diffusion coefficient corresponds to an approximate radius of gyration of 2.8 nm in dilute aqueous solution, close to that of the similar-length low complexity (LC) domain of hnRNPA2 43 and significantly more extended than the globular reference protein lysozyme (2.03 nm) ( Figure S3A), which is of almost identical molecular weight to TDP-43 CTD. At concentrations above 50 μM, however, the apparent diffusion coefficient of the CTD sample decreases, consistent with CTD assembly into higher order species.…”
Section: G335 and G338 Mutations Enhance Intermolecular Helix-helix Cmentioning
confidence: 59%
See 1 more Smart Citation
“…At low CTD concentrations (50 µM and below) the apparent diffusion coefficient for WT CTD remains largely unchanged (8.8± 0.1 · 10 -11 m 2 s -1 ) ( Figure 3C), suggesting that this value reflects the diffusion coefficient of monomeric CTD. This diffusion coefficient corresponds to an approximate radius of gyration of 2.8 nm in dilute aqueous solution, close to that of the similar-length low complexity (LC) domain of hnRNPA2 43 and significantly more extended than the globular reference protein lysozyme (2.03 nm) ( Figure S3A), which is of almost identical molecular weight to TDP-43 CTD. At concentrations above 50 μM, however, the apparent diffusion coefficient of the CTD sample decreases, consistent with CTD assembly into higher order species.…”
Section: G335 and G338 Mutations Enhance Intermolecular Helix-helix Cmentioning
confidence: 59%
“…Similarly, the contacts formed by TDP-43 CTD conserved region are also heterogeneous 32 , unlike amphiphilic α-helices that form ordered, rigid bundles. Indeed, CTD assembly may underlie the ability of this region of TDP-43 to interact with splicing factor partners including hnRNPA231,43 . Hence TDP-43 CTD conserved region serves as a dynamic and heterogeneous binding module to enhance TDP-43 phase separation.The identification of single, specific sites that can be used to substantially alter the assembly and material properties of cellular droplets offers an important opportunity to use TDP-43 CTD as a module to tune phase separation in engineered fusion proteins.…”
mentioning
confidence: 99%
“…Work from different labs has shown that both serine and tyrosine phosphorylation can control phase separation [12,52,89,90], and the same holds true for arginine methylation [49,91] and sumoylation [80]. Importantly, the activity of the dual specificity kinase DYRK3, which partitions into SG, was shown to be necessary for SG dissolution [92], suggesting that there might be specific cellular switches controlling these processes.…”
Section: Spatiotemporal Regulationmentioning
confidence: 99%
“…2 This phenomenon is similar to the mixing of water and oil or can be imagined as the process of raindrop formation over an umbrella on rainy days. 5 Recently, Ries et al 6 To address whether m 6 A regulates the phase separation of DF2 protein, the authors found that in m 6 A methyltransferase 14-knockout mouse embryonic stem cells, the formation of endogenous stress granules took place normally after exposure to heat shock; however, the localization of DF2 proteins in stress granules was significantly reduced. 3 Cells are separated from each other by phase separation to achieve a variety of biological functions.…”
Section: Introductionmentioning
confidence: 99%
“…4 The multivalent interaction of intracellular biological macromolecules is common and affected by some modifications, such as phosphorylation and methylation. 5 Recently, Ries et al 6 To address whether m 6 A regulates the phase separation of DF2 protein, the authors found that in m 6 A methyltransferase 14-knockout mouse embryonic stem cells, the formation of endogenous stress granules took place normally after exposure to heat shock; however, the localization of DF2 proteins in stress granules was significantly reduced. The localization of DF2 to stress granules under cellular stress is dependent on its modification with m 6 A.…”
Section: Introductionmentioning
confidence: 99%